Diagnostic Value of the Voltage‐to‐Mass Ratio in Biopsy‐Proven Cardiac Amyloidosis - Zihan Jiang; Shengsheng Zhuang; Min Tang; Zhuang Tian; Shuyang Zhang (Annals of Noninvasive Electrocardiology)
ABSTRACT Objectives The calculation of left ventricular mass varies in different studies, and reference values of the voltage‐to‐mass ratio for diagnosing cardiac amyloidosis (CA) are lacking. This study aimed to determine the value of the voltage‐to‐mass ratio in diagnosing CA and provide an optimal cut‐off value for different calculation methods. Methods We reviewed the electrocardiograms and echocardiograms of 213 consecutive biopsy‐proven CA patients, 236 hypertrophic cardiomyopathy (HCM) patients, 100 hypertensive heart disease patients, and 181 healthy controls. Left ventricular mass was calculated using linear and cross‐sectional area (CSA) methods. The voltage‐to‐mass ratios were compared between the CA group and other groups. The voltage‐to‐mass ratio obtained was used to build multivariate logistic regression models that predicted the log odds of developing CA. Results The CA group had a significantly lower voltage‐to‐mass ratio than the HCM, hypertensive heart disease, and healthy control groups. The voltage‐to‐mass ratio was an independent factor significantly associated with the CA diagnosis after adjusting for baseline characteristics. Linear and CSA methods yielded areas under the ROC curve of 0.86 and 0.90, respectively. Using the CSA method, the optimal cut‐off was 16.42 mV/mm2/m2, with 89.0% sensitivity and 80.8% specificity. Conclusion The voltage‐to‐mass ratio could differentiate patients with CA, HCM, and hypertensive heart disease from healthy controls, potentially providing an accurate and non‐invasive alternative to current expensive and invasive diagnostic techniques.